Exploring the transformative potential of Bluetooth beacons in higher education - Kieran McDonald; Ian Glover (Association for Learning Technology, 2016)
The growing ubiquity of smartphones and tablet devices integrated into personal, social and professional life, facilitated by expansive communication networks globally, has the potential to disrupt higher education. Academics and students are considering the future possibilities of exploiting these tools and utilising networks to consolidate and expand knowledge, enhancing learning gain. Bluetooth beacon technology has been developed by both Apple and Google as a way to situate digital information within physical spaces, and this paper reflects on a beacon intervention in a contemporary art school in higher education conducted by the authors intended to develop a situated community of practice in Art & Design. The paper describes the project, including relevant theoretical foundations and background to the beacon technology, with regards to the potential of using these devices to create a connected learning community by enhancing learning and facilitating knowledge creation in a borderless learning space.